Long-term monitoring of pesticide residues on public sites: A regional approach to survey and reduce spray drift - Prechsl, Ulrich E.; Bonadio, Martina; Wegher, Lino; Oberhuber, Michael (Frontiers in Environmental Science, 2022)
Plant protection strongly increased food safety and agricultural productivity, but with societal and environmental costs as the downside. Especially the contamination of non-target areas via spray drift represents an adverse side-effect. Residential zones and playgrounds are so-called “sensitive zones”, where spray drift is considered to have an increased potential for human health risk. To study the residue imprint potentially associated with spray drift we analyzed data of a residue monitoring program in South Tyrol (Northern Italy). From 2018 to 2021, 39 playgrounds were analyzed multiple times per year for the presence and concentration of pesticide residues on grass samples. In a total of 399 samples, we identified 39 different residues deriving primarily from agricultural production. Mean concentration (0.0645 mg kg-1, SD: ±0.1013 mg kg-1) and comparison to Maximum Residue Levels (MRLs) of food, revealed that 98.2% of the residues were in the range of MRLs and close to the analytical limit of quantification. We found that 6 out of 334 residues had relatively elevated concentrations clearly above the MRLs. Finally, a time series analysis of the study period revealed a significant decrease in the number of detected residues and their concentration by 72% and 78%, respectively. In the last year of this study, playgrounds showed on average 1.46 residues (SD: ±1.252) with a mean concentration of 0.012 mg kg-1 (SD: ± 0.025), which is almost equal to the limit of detection (0.01 mg kg-1). The presented results demonstrate that a) spray drift decreased significantly within 4-years and that b) the introduced measures to decrease spray drift have been effective. Consequently, these results imply c) that improved farming practice represents an important leverage point of further spray drift reduction.